Determinants of Employee Engagement: The Role of Work Stress, Toxic Leadership and Work–Life Balance - Ni Kadek Evita Cahyati Ningrum; Ida Ayu Oka Martini (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines the effects of work stress and toxic leadership on employee engagement, with work–life balance serving as a mediating variable among Generation Z employees in the tourism sector, particularly in hotels and restaurants in Bali. The study employed a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0. Data were collected from 150 Generation Z employees aged 17–28 years who work as permanent staff in the hospitality sector in Bali. The findings indicate that work stress positively influences both work–life balance and employee engagement, suggesting that challenging stress can function as a motivating factor that enhances adaptive behavior and involvement at work. Toxic leadership, however, negatively and significantly affects employee engagement but does not significantly influence work–life balance. Furthermore, work–life balance positively impacts employee engagement and significantly mediates the relationship between work stress and engagement. However, it does not mediate the relationship between toxic leadership and engagement, indicating that the destructive nature of toxic leadership directly reduces employees’ psychological attachment to their work. Theoretically, this study contributes to the Job Demands–Resources (JD-R) model and the Theory of Reasoned Action (TRA) by distinguishing between constructive job demands and destructive leadership behaviors in shaping engagement. Practically, the findings highlight the importance of adaptive stress management, leadership development, and work–life balance policies in sustaining Generation Z employee engagement in the hospitality industry.